Influência do ambiente do bico-de-contato na soldagem FCAW subaquática molhada com tocha especial - Marcelo Teodoro Assunção (2023)
Underwater flux-cored arc welding has been investigated in many researches due to its operational characteristics. The process is a feasible alternative to shielded metal electrodes once it provides higher deposition rates and makes possible to change the flux composition. When compared to open air welding, the conventional method of underwater flux-cored arc welding (UWW-FCAW) is characterized by water around the welding torch’s electric parts, the tubular wire, the molten pool and the workpiece. Current and voltage electric signal show worse stability due to the water environment, to bubble evolution and detachment phenomenom and also to the water pressure in higher depths. In the present work, underwater FCAW was performed by keeping the contact tip dry, inside a specially developed torch, and as in conventional underwater welding. The welds were carried out in a flat position at simulated depths of 0.3 m, 10 m and 30 m using a hyperbaric chamber. Welding electrical signals of voltage, current and contact tip temperature were acquired and processed to determine process behavior. As a result, the welding current was reduced when the contact tip was kept dry inside the torch because of the higher temperature achieved by resistance heating when it was insulated from the water. The ambient surrounding the contact tip interfered with the coefficient of heat transfer and, consequently, with its temperature. Welds performed with the dry contact tip also presented slight variations in bead shape parameters in different water depths. Higher arc stability was achieved by welding with the contact tip inside the air chamber, as minor variations of electric signals and fewer arc extinction events were observed compared to conventional underwater welds. The combination of improved arc stability with higher electrode temperature may also have contributed to minor porosity and smaller variation of the reinforcement along the weld bead.